Improving De-Escalation Strategy: Monitoring Control, Bonus Incentive and Escalation of Commitment - Kasingku, Frisky Jeremy (Riset Akuntansi dan Keuangan Indonesia, 2020)
Managers continue to perform irrational behavior by escalating the wrong decision hoping that the situation will change. The irrational escalation of commitment brings negative influences on organization performance. Previous studies have found several mitigation strategies. One of the strategies found is called monitoring control in private information situations. However, this strategy has not considered the agency problem that can occur between owners and managers. For this reason, this study seeks to improve the de-escalation monitoring strategy by adding agency theory. The Experimental method with factorial design of 2x2x2 is applied to answer research problem. The first factor is information (public vs private), the second factor is monitoring control (present vs absent) and the third factor is bonus incentive (present vs absent). The participants in this study were 159 undergraduate students who were taking principles of investment course. As a result, there are interaction effects from the variables of monitoring control, information availability, and bonus incentive. The interaction effect distinguishes participants in making decisions. Companies can consider giving monitoring control and bonuses together to differentiate managers’ decisions when assessing projects. Further study may explore more detail on the bonus procedures with more in-depth bonus mechanism.